Dual Ag/Co cocatalyst synergism for the highly effective photocatalytic conversion of CO2 by H2O over Al-SrTiO3. Issue 13 (2nd March 2021) - Wang, Shuying; Teramura, Kentaro; Hisatomi, Takashi; Domen, Kazunari; Asakura, Hiroyuki; Hosokawa, Saburo; Tanaka, Tsunehiro
Abstract : Deposition Ag and Co dual cocatalysts onto Al-SrTiO3 significantly improves its activity for photoreduction of CO2 by H2 O, with extremely high selectivity to CO evolution (99.8%), in which Ag and Co enable CO2 reduction and H2 O oxidation, respectively. Abstract : Loading Ag and Co dual cocatalysts on Al-doped SrTiO3 (AgCo/Al-SrTiO3 ) led to a significantly improved CO-formation rate and extremely high selectivity toward CO evolution (99.8%) using H2 O as an electron donor when irradiated with light at wavelengths above 300 nm. Furthermore, the CO-formation rate over AgCo/Al-SrTiO3 (52.7 μmol h −1 ) was a dozen times higher than that over Ag/Al-SrTiO3 (4.7 μmol h −1 ). The apparent quantum efficiency for CO evolution over AgCo/Al-SrTiO3 was about 0.03% when photoirradiated at a wavelength at 365 nm, with a CO-evolution selectivity of 98.6% (7.4 μmol h −1 ). The Ag and Co cocatalysts were found to function as reduction and oxidation sites for promoting the generation of CO and O2, respectively, on the Al-SrTiO3 surface.